Effects of Biochar on Soil Organic Carbon Stability in Degraded Alpine Grasslands—A Study on Arid Regions in Central Asia - Yunpeng Hu; Maidinuer Abulaizi; Yuxin Tian; Yang Hu; Mo Chen; Keyi Li; Yuanbin Jia; Tianle Kou; Jianqin Zhou; Hongtao Jia (Land)
Numerous studies have reported the importance of soil organic carbon (SOC) in grassland ecosystems and its response to soil degradation, but the effect of biochar application on SOC pools in degraded alpine grasslands remains unclear. Here, we set up nine biochar addition treatments with a combination of three different biochar particle sizes (0~0.25 mm, 0.25~1 mm, and 1~2 mm) and three different biochar additions (1%, 2%, and 4%), and conducted a short-term observational experiment over a 7-month period in the non-degraded (ND), lightly degraded (LD), and severely degraded (SD) zones of alpine grassland. The results showed that the addition of 0.25~1 mm/2% and 1~2 mm/4% biochar increased the SOC storage in LD and SD by 2.03 kg m−2 and 1.19 kg m−2, respectively. The addition of biochar decreased the stability of the soil carbon pools, but the stability of the soil carbon pools increased with time. The results of structural equation modeling (SEM) indicated that changes in biochar application and particle size would indirectly affect the stability of soil carbon pools by influencing soil and plant indicators, while changes in electrical conductivity (EC) were the key factors influencing the changes of soil carbon pools in degraded LD and SD grasslands. These results can provide technical support and theoretical basis for realizing the benign development of degraded alpine grassland ecosystems and the “carbon neutral” strategy in arid areas.